Age-Stratified Analysis of Vaginal Microbiota Dysbiosis and the Relationship with HPV Viral Load in HPV-Positive Women - Mingzhu Li; Chao Zhao; Yun Zhao; Jingran Li; Lihui Wei (Journal of Immunology Research)
Objective. This study evaluated the distribution of vaginal microbiota dysbiosis and the association with HPV viral load test in high-risk HPV-positive women before and after 50 years old. Methods. For this cross-sectional study, 388 HPV-positive women prior to referral to colposcopy in Peking University Peoples’ Hospital were included and classified as younger than 50 years (n=307) and aged 50 years or older (n=81), midvagina bacterial community composition was characterized by FlashDetect™ MAX vaginal microbe detection kit, and BMRT-HPV reported type-specific viral loads/10,000 cells. Results. The community state type (CST) IV was the most common CST occurring in 148 women (38.1%). The proportion of CST IV in those aged 50 years or older was significantly higher than those younger than 50 years (women) (66.7% vs. 30.6%); the difference was statistically significant (<0.001). CST distribution has no statistical difference in different grades of cervical lesion, regardless of the age (p=0.238 and 0.263). However, the women with high-grade cervical lesion presented a more complicated trend and the abundance of vaginal microbiota dysbiosis than low-grade lesion. HPV16/18 viral load was found to be significantly higher in CST III and CST IV than CST I/II/V (p<0.05)in women younger than 50 years. Conclusions. In women younger than 50 years, higher HPV16/18 load was more closely associated with CST IV; however, it had no significant correlation in women aged 50 years or older.